2001
DOI: 10.1109/20.952613
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic vector hysteresis represented by superposition of stop hysteron models

Abstract: The present paper first shows that the scalar stop hysteron model has the property of equal vertical chords for back-andforth input variations of the same amplitude. This property leads to an identification method of the scalar model. Secondly, identification methods are developed for the 3-D and 2-D isotropic vector models that are constructed by the superposition of scalar stop hysteron models. Numerical simulations show that these methods identify the scalar and vector models satisfactorily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 8 publications
0
44
0
Order By: Relevance
“…It is assumed that the input has no extrema other than . A previous work [15], [16] has shown that the vertical difference between does not depend on (6) In other words, the back-and-forth input variations of the same amplitude produce equal vertical chords regardless of the dc bias. A previous study [17] has shown that magnetic characteristics of a silicon steel sheet do not satisfy the property of equal vertical chords regardless of dc bias.…”
Section: Stop Model and Property Of Equal Vertical Chords Regardlmentioning
confidence: 99%
See 4 more Smart Citations
“…It is assumed that the input has no extrema other than . A previous work [15], [16] has shown that the vertical difference between does not depend on (6) In other words, the back-and-forth input variations of the same amplitude produce equal vertical chords regardless of the dc bias. A previous study [17] has shown that magnetic characteristics of a silicon steel sheet do not satisfy the property of equal vertical chords regardless of dc bias.…”
Section: Stop Model and Property Of Equal Vertical Chords Regardlmentioning
confidence: 99%
“…However, the function , given by (1) and (2), has a hysteretic property even when . In order for to become a single-valued function when , the operator is defined as the following: The stop model (1) has the property of equal vertical chords regardless of dc bias [15], [16] as follows. Let and be the outputs on ascending and descending curves, respectively, for a back-and-forth input variation given by (5) having amplitude (5) where is an arbitrary dc bias (see Fig.…”
Section: Stop Model and Property Of Equal Vertical Chords Regardlmentioning
confidence: 99%
See 3 more Smart Citations